A note on Agraeciini species (Orthoptera: Tettigoniidae: Conocephalinae) in India - Nagar, Rajendra; Swaminathan, Tatiana; Swaminathan, R. (Zootaxa, 2016)
The present paper re-describes three known species of the tribe Agraeciini (Tettigonidae: Conocephalinae), as well as recording Palaeoagraecia brunnea Ingrisch, 1998 for the first time from India. These descriptions hold to be useful in the identification of Indian agraeciine species. The important morphological characters of the head, pronotum, cerci, spines on the fore tibiae, hind femora and the ovipositor have been illustrated with suitable line drawings to distinguish the newly reported species.